Three Faiths — One God - Meltzerd. author. aut Link
XIV, 240 p.
Keywords: The interactions of the Jewish, Christian and Muslim communities through the centuries have often been hostile and sometimes violent. Today a new 'trialogue' between them is developing in several parts of the world. One of the most ambitious ventures so far of this kind took place recently in California and produced this set of exploratory papers and responses. The subjects are the concepts of God in the three traditions, their attitudes to the material world, and their understandings of human life and history. The discussions were frank and realistic but at the same time hopeful.